PEMBERDAYAAN MASYARAKAT DALAM PENERAPAN CHS DI DESA SIKASUR KABUPATEN PEMALANG DI ERA NEW NORMAL - Julian Andriani Putri; Wenefrida Ardhian Ayu Hardiani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2021)
The Covid-19 pandemic has had a significant impact on all industrial sectors in Indonesia, and one of them is the country's tourism sector since the beginning of 2020 and consequently has had a tremendous impact on tourism villages in Indonesia. A survey conducted by the Desa Wisata Institute (2020) of 97 tourist villages throughout Indonesia noted that no less than 92.8% of villages (or around population in these villages continued to maintain their profession. the original. It is undeniable that tourism contributes a large amount of income so that this pandemic has caused the tourist villages to suffer losses of tens to hundreds of millions of rupiah. Nearly 99% of tourism villages in Indonesia were closed due to the implementation of social restriction policies which resulted in the cancellation of visiting guests and in the end it had a long-term effect on tourism entrepreneurs in tourist villages such as restaurant entrepreneurs, homestay owners, craftsmen, artists. For this reason, in order to help revive the existence of the Tourism Village in the community, in the community service of STIEPARI Semarang this time the goal is in Sikasur Village, Pemalang Regency, this program was held with the aim of helping tourist villages raise their ranks and providing a forum for community service for the academics involved. CHS (Cleanliness, Health, Safety) which in the new normal era is considered very important to be implemented in various tourist destinationsThese community service activities include location surveys, Forum Group Discussion (FGD), and outreach. The results of this activity are expected to make Sikasur Tourism Village begin to adapt and develop in this new normal era